2014
DOI: 10.1158/1055-9965.epi-14-0437
|View full text |Cite
|
Sign up to set email alerts
|

Eye Cancer Incidence in U.S. States and Access to Fluoridated Water

Abstract: Environmental risk factors for uveal melanomas (cancer of the iris, ciliary body, and choroid) have not been identified. To search for these, we examined the correlation of age-adjusted eye cancer incidence rates, a surrogate for uveal melanoma rates, in U.S. states with group level geographic and demographic factors using multivariate linear regression. Incidence rates for eye cancer were inversely correlated with the percentage of the population receiving fluoridated water; that is, higher rates were found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
(33 reference statements)
0
6
0
1
Order By: Relevance
“…All sites 3 [10,11,19] Digestive organs 4 [10,11,20,21] Respiratory organs 4 [10,11,19,20] Urinary organs 4 [10,11,19,20] Hormonal and/or reproductive organs 4 [10,11,19,20] Bone 8 [10,11,[13][14][15][16][17]22] Brain and nerves 3 [10,11,15] Blood and lymph 3 [11,15,19] Lip and skin 1 [11] Eye cancer 1 [18] *Some articles investigated more than 1 cancer site…”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…All sites 3 [10,11,19] Digestive organs 4 [10,11,20,21] Respiratory organs 4 [10,11,19,20] Urinary organs 4 [10,11,19,20] Hormonal and/or reproductive organs 4 [10,11,19,20] Bone 8 [10,11,[13][14][15][16][17]22] Brain and nerves 3 [10,11,15] Blood and lymph 3 [11,15,19] Lip and skin 1 [11] Eye cancer 1 [18] *Some articles investigated more than 1 cancer site…”
Section: Referencesmentioning
confidence: 99%
“…[9] For example, there is an ongoing debate in the scientific community about the role of fluoridated water in cancer development in humans; and different epidemiological studies had been conducted to establish or refute this relationship. [10][11][12][13][14][15][16][17][18][19][20][21][22] While some studies reported no relationship between fluoridated water consumption and cancer occurrence, others reported a direct or an inverse relationship between them. [10][11][12][13][14][15][16][17][18][19][20][21][22] Despite the significant quantity of epidemiological studies that had investigated the relationships between community water fluoridation and human cancers, no known study has the quantity of the existing epidemiological evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As taxas de incidência de câncer de olho foram inversamente correlacionadas com a porcentagem da população que recebe água fluoretada; ou seja, taxas maiores deste tipo de câncer foram encontradas em estados com menores prevalências de fluoretação. Os pesquisadores hipotetizaram que o flúor, sendo conhecido por inibir o crescimento dos agentes microbianos que causam lesões coróides e coroidites em animais, poderia estar produzindo o mesmo efeito em humanos (Schwartz 2014).…”
Section: Câncer?unclassified
“…However, when the melanoma does not metastasize to other parts of the body, the five years’ relative survival rate is about 80%. If the melanoma metastasized to distant parts of the body, the 5 years relative survival rate will be about 15% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%